Scaffolding knowledge. Issue 1 (23rd October 2022) - Tanesini, Alessandra
Abstract: In this article I argue that often propositional knowledge is acquired and retained by extensive reliance on physical and social scaffolds that create an environment or niche conducive to knowledge. It is incumbent on epistemologists to subject these aids to epistemic assessments. I show that several of the activities involved in the creation of niches within which inquiry can thrive are carried out by whole cultures. New generations benefit from inheriting these niches whilst being able to improve upon them to the advantage of their descendants. Finally, I highlight that the growth of human epistemic achievements is often due to increased outsourcing of cognitive effort and epistemic powers onto impersonal physical and social structures so that human beings can succeed more by contributing less to the solution of problems.